Improved magnetic induction tomography - Turton, Logan James (2023)
Imaging through magnetic induction has inherent advantages over rival technologies, including being safe, contactless, and capable of both the location and characterisation of underlying electrical properties. Applications are wide-ranging, varying from geophysical investigations of the sub-surface, through security screening of baggage, to medical imaging. This research aims to improve the quality of image reconstructions from inversion.